Genome-Wide Identification of Mango (Mangifera indica L.) Polygalacturonases: Expression Analysis of Family Members and Total Enzyme Activity During Fruit Ripening - Dautt-Castro, Mitzuko; López-Virgen, Andrés G.; Ochoa-Leyva, Adrian; Contreras-Vergara, Carmen A.; Sortillón-Sortillón, Ana P.; Martínez-Téllez, Miguel A.; González-Aguilar, Gustavo A.; Casas-Flores, J. Sergio; Sañudo-Barajas, Adriana; Kuhn, David N.; Islas-Osuna, Maria A. (Frontiers in Plant Science, 2019)
Mango (Mangifera indica L.) is an important commercial fruit that shows a noticeable loss of firmness during ripening. Polygalacturonase (PG, E.C. 3.2.1.15) is a crucial enzyme for cell wall loosening during fruit ripening since it solubilizes pectin and its activity correlates with fruit softening. Mango PGs were mapped to a genome draft using seventeen PGs found in mango transcriptomes and 48 bonafide PGs were identified. The phylogenetic analysis suggests that they are related to Citrus sinensis, which may indicate a recent evolutive divergence and related functions with orthologs in the tree. Gene expression analysis for nine PGs showed differential expression for them during postharvest fruit ripening, MiPG21-1, MiPG14, MiPG69-1, MiPG17, MiPG49, MiPG23-3, MiPG22-7 and MiPG16 were highly up-regulated. PG enzymatic activity also increased during maturation and these results correlate with the loss of firmness observed in mango during postharvest ripening, between the ethylene production burst and the climacteric peak. The analysis of PGs promoter regions identified regulatory sequences associated to ripening such as MADS-box, ethylene regulation like ethylene insensitive 3 (EIN3) factors, APETALA2-like and ethylene response element factors. During mango fruit ripening the action of at least these nine polygalacturonases contribute to softening, and their expression is regulated at the transcriptional level. The prediction of the tridimensional structure of some PGs showed a conserved parallel beta-helical fold related to polysaccharide hydrolysis and a modular architecture where exons correspond to structural elements. Further biotechnological approaches could target specific softening-related PGs to extend mango postharvest shelf life.